Accounting for Micro and Small Entrepreneurs and Medium (MSMEs) - adriyana nuryadin; Alimuddin; Syarifuddin (LP2M IAIN Palopo, 2026)
This research aims to explore and understand the meaning of accounting from the perspective of MSME entrepreneurs. So far, accounting has often been imposed as a standard-based formal practice (SAK EMKM) which is often rejected or not applied by MSME actors. This research uses a qualitative approach to explore and understand the meaning of accounting from the perspective of MSME actors. Data were obtained through in-depth interviews, observations, and documentation of purposively selected informants. All transcribed interview results are then processed and analyzed using NVivo software. Data analysis is carried out in stages through the process of coding, theme identification, and data visualization using the Word Cloud feature to obtain an overview of the most dominant words, concepts, and meanings in MSMEs' understanding of accounting. The results of the study show that MSME actors interpret accounting and bookkeeping practically as a recording and business financial management activity. Based on Word Cloud analysis, this meaning consistently focuses on daily transaction activities, such as recording income, expenses, purchases, and sales that occur in business operations. The findings of this study are expected to contribute to the development of behavioral accounting literature and become a consideration for regulators in formulating policies that are more relevant to the local context of MSMEs.